Legal and Ethical Issues around Incorporating Traditional Knowledge in Polar Data Infrastructures. (3rd February 2017) - Scassa, Teresa; Taylor, Fraser
Human knowledge of the polar region is a unique blend of Western scientific knowledge and local and indigenous knowledge. It is increasingly recognized that to exclude Traditional Knowledge from repositories of polar data would both limit the value of such repositories and perpetuate colonial legacies of exclusion and exploitation. However, the inclusion of Traditional Knowledge within repositories that are conceived and designed for Western scientific knowledge raises its own unique challenges. There is increasing acceptance of the need to make these two knowledge systems interoperable but in addition to the technical challenge there are legal and ethical issues involved. These relate to 'ownership' or custodianship of the knowledge; obtaining appropriate consent to gather, use and incorporate this knowledge; being sensitive to potentially different norms regarding access to and sharing of some types of knowledge; and appropriate acknowledgement for data contributors. In some cases, respectful incorporation of Traditional Knowledge may challenge standard conceptions regarding the sharing of data, including through open data licensing. These issues have not been fully addressed in the existing literature on legal interoperability which does not adequately deal with Traditional Knowledge. In this paper we identify legal and ethical norms regarding the use of Traditional Knowledge and explore their application in the particular context of polar data. Drawing upon our earlier work on cybercartography and Traditional Knowledge we identify the elements required in the development of a framework for the inclusion of Traditional Knowledge within data infrastructures.